2014
DOI: 10.1159/000362857
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Prognostic Factors in Primary Peritoneal Carcinoma: A Multicenter Study of the Anatolian Society of Medical Oncology (ASMO)

Abstract: Background: In this study, we aimed to evaluate the clinicopathological characteristics and prognosis of patients with primary peritoneal carcinoma (PPC), and the effectiveness and toxicity of first-line platinum/taxane combination therapy. Patients and Methods: We retrospectively evaluated 79 patients with PPC, who were treated and followed up between December 2001 and August 2012 at 10 medical oncology clinics. Results: All patients were female, with a median age of 63 years (range 34-79 years). Histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…The study also demonstrated no statistically significant difference in OS between group A and group B, which suggests that CRS þ HIPEC is equally effective in treating PPSC regardless of whether it is performed as the first treatment or at recurrence. Several case studies, and small-sample retrospective studies [3,9,[27][28][29][30][31][32][33][34], a single-institution large-sample retrospective study [11], and two prospective studies [4,35] have reported median OS ranging from 17.0-101.7 months for PPSC patients (Table 3). A systemic review by Pentheroudakis et al [10] evaluated 25 clinical trials on PPSC in three time periods: before 1990, when platinum-and alkylator-based chemotherapy were considered standard, during the 1990s, when platinum combinations without taxanes were the standard treatment, and after 1995, when platinum/taxane combinations were the standard therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also demonstrated no statistically significant difference in OS between group A and group B, which suggests that CRS þ HIPEC is equally effective in treating PPSC regardless of whether it is performed as the first treatment or at recurrence. Several case studies, and small-sample retrospective studies [3,9,[27][28][29][30][31][32][33][34], a single-institution large-sample retrospective study [11], and two prospective studies [4,35] have reported median OS ranging from 17.0-101.7 months for PPSC patients (Table 3). A systemic review by Pentheroudakis et al [10] evaluated 25 clinical trials on PPSC in three time periods: before 1990, when platinum-and alkylator-based chemotherapy were considered standard, during the 1990s, when platinum combinations without taxanes were the standard treatment, and after 1995, when platinum/taxane combinations were the standard therapy.…”
Section: Discussionmentioning
confidence: 99%
“…PPSC is a rare and heterogeneous tumour that is diagnosed at approximately one tenth the frequency of epithelial ovarian cancer [2]. PPSC is an extra-ovarian malignancy that spreads widely inside the peritoneal cavity, primarily in the omentum and peritoneal surface with intact ovaries or minimal ovarian involvement, and is found predominantly in elderly and post-menopausal women [3,4]. This malignancy is also diagnosed in women many years after an oophorectomy for benign diseases or a prophylactic oophorectomy in women with a hereditary susceptibility to ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A total peritonectomy (residual tumor <1-2 cm) is feasible in 13-79% of patients and should be performed to remove precursor sites and microscopic residual disease (98). Complete resection sorts out one of the most important prognostic factors affecting survival as residual tumors are reported in 60% of grossly normal-appearing peritoneum (99)(100)(101). The rates of lymph node involvement are similar between SPPC and primary ovarian tumor however the approach for lymph node dissection is different between the two entities.…”
Section: Question 4: Is the Treatment Of Sppc Different From That Of Primary Ovarian Cancer?mentioning
confidence: 99%
“…The optimal treatment of PPSC is surgical resection and chemotherapy, with platinum-based chemotherapy used most commonly (10). Intraperitoneal chemotherapy has recently demonstrated a survival benefit in patients with PPSC when compared to those treated with surgery alone or surgery in combination with systemic chemotherapy (11).…”
Section: Discussionmentioning
confidence: 99%